Early treatment with anti-α4β7 antibody facilitates increased gut macrophage maturity in SIV-infected rhesus macaques - Johnson, Samuel D.; Knight, Lindsey A.; Kumar, Narendra; Olwenyi, Omalla A.; Thurman, Michellie; Mehra, Smriti; Mohan, Mahesh; Byrareddy, Siddappa N. (Frontiers in Immunology, 2022)
Despite advances in combination antiretroviral therapy (cART), people living with HIV (PLWH) continue to experience gastrointestinal dysfunction. Infusions of anti-α4β7 monoclonal antibodies (mAbs) have been proposed to increase virologic control during simian immunodeficiency virus (SIV) infection in macaques with mixed results. Recent evidence suggested that the therapeutic efficacy of vedolizumab (a humanized anti-α4β7 mAb) during inflammatory bowel diseases depends on microbiome composition, myeloid cell differentiation, and macrophage phenotype. We tested this hypothesis in SIV-infected anti-α4β7 mAb treated macaques and provided flow cytometric and microscopic evidence that anti-α4β7 administered to SIV-infected macaques increases the maturity of macrophage phenotypes typically lost in the small intestines during SIV disease progression. Further, this increase in mature macrophage phenotype was associated with tissue viral loads. These phenotypes were also associated with dysbiosis markers in the gut previously identified as predictors of HIV replication and immune activation in PLWH. These findings provide a novel model of anti-α4β7 efficacy offering new avenues for targeting pathogenic mucosal immune response during HIV/SIV infection.